New or poorly known West Palaearctic Meessiidae (Lepidoptera: Tineoidea) - R. Gaedike (SHILAP, 2020)
Three species of Meessiidae are described as new to science: Eudarcia albocapitata Gaedike sp. n., Eudarcia lakoniacola Gaedike sp. n. and Infurcitinea mayri Gaedike, sp. n. The hitherto unknown female genitalia of Infurcitinea olympica Petersen, 1958 are described and illustrated for the first time. The first records of several species from various countries are published.